PENGARUH BRANDING DAN DIGITAL MARKETING TERHADAP UPAYA OPTIMALISASI PEMASARAN BAGI PELAKU USAHA MIKRO KECIL MENENGAH - Ridwansyah, Muhammad (JURNAL LENTERA BISNIS, 2025)
This research activity was conducted to help explain the steps that need to be taken by UMKM stakeholders to develop digital branding and marketing strategies to optimize their businesses. One of the problems faced by most UMKM is the lack of understanding of branding and digital marketing in optimizing the marketing of their products as a function of maintaining business sustainability, that branding is not only about marketing. The method used is qualitative descriptive, aiming to describe each stage of the process carried out to provide a cognitive and emotional impact applied to their UMKM, provide socialization and training on how to improve knowledge, insights, skills, and awareness and motivate the community, especially UMKM actors in local-based economic development which can be done by increasing the selling value of local products so that they can increase community income by means of product branding. In conclusion, UMKM actors can create their product branding by selling through social media and applying innovations to their packaging.